2017
DOI: 10.1634/theoncologist.2017-0278
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of 18F-Fluorodeoxyglucose Positron Emission Tomography in the Diagnostic Algorithm of Advanced Entero-Pancreatic Neuroendocrine Neoplasms

Abstract: The findings of the present study may help physicians dealing with advanced neuroendocrine neoplasms to select patients for whom F-fluorodeoxyglucose positron emission tomography is useful to predict poor clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Given their high proliferative activity and low expression of SSTRs, poorly differentiated NETs are commonly imaged by 18 F‐fluorodeoxyglucose PET/CT. In well‐differentiated NETs 18 F‐fluorodeoxyglucose PET uptake can correlate negatively with prognosis; however, the use of this imaging modality is not routinely recommended …”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Given their high proliferative activity and low expression of SSTRs, poorly differentiated NETs are commonly imaged by 18 F‐fluorodeoxyglucose PET/CT. In well‐differentiated NETs 18 F‐fluorodeoxyglucose PET uptake can correlate negatively with prognosis; however, the use of this imaging modality is not routinely recommended …”
Section: Diagnosismentioning
confidence: 99%
“…In well-differentiated NETs 18 F-fluorodeoxyglucose PET uptake can correlate negatively with prognosis; however, the use of this imaging modality is not routinely recommended. 91,92…”
Section: Diagnosismentioning
confidence: 99%
“…Indeed, in the last few years, the role of 18F-FDG PET/CT in these neoplasms has emerged as an important tool to define tumor aggressiveness and give relevant prognostic information especially in the management of G3 NEN [7,37]. In fact, it has been well demonstrated that 18F-FDG PET/CT has a high diagnostic accuracy to identify progression of disease with unfavorable clinical outcomes in patients with advanced GEP NEN [38]. In addition, its recently emerging the potential role of 18F-FDG PET/CT in predicting response to PRRT in advanced NEN [39][40][41].…”
Section: Imaging Investigationsmentioning
confidence: 99%
“…Although its usefulness in NET is limited due to the low glycolytic activity of these cancer cells, positive 18 FDG imaging often foreshadows a more aggressive disease course. 24…”
Section: Radioligand Theranostics For Somatostatin Receptorpositive Netsmentioning
confidence: 99%